The Effect of Population Administration Quality on Community Satisfaction in the Village Government - Ulfa Maisaroh; Hendra Sukmana (Indonesian Journal of Cultural and Community Development, 2022)
The implementation of public services must have service standards, as a guarantee of certainty for local governments in serving the community or the public in general in carrying out their duties and functions and for service recipients in the process of submitting their application. The purpose of the study was to influence the quality of population administration on community satisfaction in the government of Ploso Village, Wonoayu District, Sidoarjo Regency. This type of research uses descriptive quantitative analysis method. The number of samples as many as 188 respondents using non-probability sampling technique with the type of accidental sampling. Sources of data used using primary data with a questionnaire. The analysis technique used is multiple linear regression with t and f test tools. The results of the t-test study found that the variables of responsiveness, reliability, assurance, empathy, tangibles had a positive and significant influence on community satisfaction, this can be proven that the significance value is more than 0.05. The results of the joint test show that the service quality variables which include the dimensions of Responsiveness, Reability, Assurance, Empathy and Tangible have a positive and significant effect on community satisfaction in the Ploso Village Government, Wonoayu District, Sidoarjo Regency, this is evidenced by the obtained Fcount of 124.578 , a significance value of 0.000 < : 0.05. The results of the multiple correlation coefficient test (R) of 0.797 indicate that the correlation between the dimensions of Responsiveness, Reability, Assurance, Empathy and Tangible to community satisfaction in the Ploso Village Government, Wonoayu District, Sidoarjo Regency has a strong linear relationship. For the analysis of the coefficient of determination (R2) is 0.635, meaning that changes in community satisfaction (Y) can be explained by the quality of service which includes changes in the dimensions of Responsiveness, Reability, Assurance, Empaty and Tangible together by 63.5%. It is hoped that the research results can be used as input for the village government in improving service quality.